1998
DOI: 10.1137/s0036142995291019
|View full text |Cite
|
Sign up to set email alerts
|

A Neumann--Neumann Domain Decomposition Algorithm for Solving Plate and Shell Problems

Abstract: We present a new Neumann-Neumann-type preconditioner of large scale linear systems arising from plate and shell problems. The advantage of the new method is a smaller coarse space than those of earlier methods of the authors; this improves parallel scalability. A new abstract framework for Neumann-Neumann preconditioners is used to prove almost optimal convergence properties of the method. The convergence estimates are independent of the number of subdomains, coefficient jumps between subdomains, and depend on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 25 publications
1
64
0
Order By: Relevance
“…Most of the early theoretical and numerical work has been carried out for scalar symmetric positive definite second order problems; see for example [6], [13]- [15], [23]. Then, the method was extended to other problems, like the advection-diffusion equations [1,7], plate and shell problems [27] or the Stokes equations [26,22].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the early theoretical and numerical work has been carried out for scalar symmetric positive definite second order problems; see for example [6], [13]- [15], [23]. Then, the method was extended to other problems, like the advection-diffusion equations [1,7], plate and shell problems [27] or the Stokes equations [26,22].…”
Section: Introductionmentioning
confidence: 99%
“…Many numerical verifications have confirmed that property. For fourth-order problems (plates and shells), displacement continuity at the "corners" of the substructures must be enforced in the macrospace in order to maintain scalability [39,40]. Since the coarse problem at the corner is sufficient to ensure the invertibility of the Steklov operators, strategies such as the FETI-DP [26] and the BDDC [41,42] enable one to remove the rigid-body modes from the macrospace.…”
Section: Comparison With Other Multiscale Strategiesmentioning
confidence: 99%
“…In an implementation of the BDD preconditioner (3), (9) , it is advantageous to use an initial approximation as u B0 = R 0 S −1 0 R T 0 g, then the Step 1 and Step 2 in every iteration can be omitted since after using the residual of the initial approximation in the Step 1, the unknown vector λ becomes the zero vector. As a result, the BDD preconditioner Eq.…”
Section: Construction Of the Bdd Preconditionermentioning
confidence: 99%
“…This method is introduced by Mandel (3) by adding a coarse problem to an earlier method of De Roeck and Le Tallec (4) known as the NeumannNeumann method and then is extended for problems with large jumps in coefficients (5) . Mandel's BDD algorithm is now exclusively employed for the solution of huge structural problems (6) , Stokes problems (7) , semiconductor simulation (8) and plate and shell problems (9) . While this method shows good performances to solve large scale elastic problems (10) , it still suffers from the high computation costs and the large required memory to solve the 3-dimensional heat conductive problems (11) .…”
Section: Introductionmentioning
confidence: 99%